PENGARUH IMPLEMENTASI CUSTOMER RELATIONSHIP MARKETING TERHADAP LOYALITAS TAMU MENGINAP DI PREMIER BASKO HOTEL PADANG - Yesi Elsandra; Silvia Rahayu (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2013)
The goal of this research is to know whether customer relationship marketing implementation influenced to guest stay loyality in Premier Basko Hotel. This research using primary and secondary data by purposive sampling method with the number of 100 respondent which is defined by Slovin formula. The result of this research shows that customer relationship marketing implementation have positive influence to guest stay in Premier Basko Hotel.